Budaya Organisasi Islami dalam Membentuk Iklim Sekolah yang Kondusif di Madrasah - Sabrifha, Eli (CV. Kurnia Grup, 2025)
This article aims to analyze how Islamic organizational culture contributes to creating a conducive school climate in madrasas. The study uses a systematic literature review approach to primary sources in the form of scientific journals and academic books. The data collection stages include identifying sources through academic databases, filtering based on topic relevance and scientific quality, and final selection based on novelty and depth of analysis. Data are analyzed through thematic analysis to identify value patterns, conceptual synthesis, and development of a theoretical framework. The analysis results reveal five pillars of Islamic organizational culture: sincerity, trustworthiness, deliberation, spiritual discipline, and exemplary behavior (uswah hasanah), which synergistically create a harmonious, participatory, noble-moral school climate conducive to holistic learning. These findings emphasize that Islamic education management must be rooted in value transformation, not merely procedural compliance, and provide a conceptual contribution to the development of a values-based madrasa model in the contemporary era.